(3eGdGjSY GdWHjH Lgdgs - (3jhSa Hf ESeGYjd Hf EdjGS Hf CMeO, CHh GdeMGSf, fUjQ GdOjf GdNhjj GdTGaYqj GdHZOGOj GdeYQha HGHf GdcJHj,J (B754 (3g` s ((3Ydi Hf CMeO Hf MSjf Hf UGdM s)
(3ChdgG (B:s
(3GdMeO ddg GdPi dGJcJHg MbjbI eYQaJg GdYdhe hGdCagGe hHYO aEfg deG cGf GdEfSGf Hd GdMjhGf LedI ef GdeQcHGJ GdYfUQjI s
(3BNQgG (B:s
(3hEf cGfJ CTHgg HGdeQcHGJ NUhUkG eG EPG CVja Edjg TF ef ZjQ Cf jchf YUGQg eWHhN s
(3HgG fXGe GdJYbjHIs
(3jdjg aGFOIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B9 - (3U (B288 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B144s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1575s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs